Problems in Teaching English to Young Learners and Their Solutions - Mukti Muhammad; Sugirin (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2024)
This study was conducted in an English lesson for kids in Garut, West Java, Indonesia. The goal of this study was to understand the teacher's viewpoint on the problem in teaching English for young students. For this study, qualitative researchers are used to conduct in-depth analyses of the data. By direct observation and interviews, teachers gather data. Teaching English in young students is a challenging task for teachers. There are issues with class management, the use the monotonous media, various student characteristics, and language proficiency. This research is supported by methods and solutions to challenges.